Study of Interaction and Solubility Parameters of Alkyl Methacrylate Polymers by Inverse Gas Chromatography - Kaya, Ismet; Ozdemir, Eyup; Coskun, Mehmet (Tubitak Scientific & Technological Research Council Turkey, 1996)
Flory-Huggins interaction parameters (x) and partial molar free energies of mixing (Delta G(1)(infinity)) have been determined by inverse gas chromatography (i.g.c.) at temperatures 413-443 K for alkanes, acetates, ketones, aromatics, THF and methanol to estimate the polymer solubility parameters (delta(2)) of PMMA, PEMA, PIBMA and Pt -BMA. Furthermore, weight fraction activity coefficients (alpha l/w(1))(infinity) of probes were calculated at infinite dilution at 413-443 K.